Effect of virtual education on health responsibility of overweight students during the COVID-19 pandemic - Sahar MahjoubVagheae Dashti; FatemehSadat SeyedNematollah Roshan; Marjan AkhavanAmjadi (BMC, 2024)
Abstract Background The global prevalence of obesity is increasing not only in adults but also in children and adolescents. In addition to the role of genetic and biological factors, policies such as the need for quarantine during the coronavirus epidemic and the family's behavioral and socioeconomic status in causing obesity cannot be ignored. The current research aimed to investigate the effect of virtual education programs on the health responsibility of overweight students during the outbreak of the Coronavirus. Methods This was a semi-experimental study with a pre-test-post-test design and a randomized control group, which was conducted in three stages)pre-intervention, intervention, and post-intervention) during 2021-22 in Tehran Province, Iran. The samples were 60 adolescent girls aged 12-18 with a body mass index higher than 25 and placed in two test and control groups through random cluster sampling. Data was collected using the demographic information profile and the 12-item health responsibility questionnaire from HPLPII. The intervention was implemented as 6 virtual training sessions of 1.5 h for the test group. After 1.5 months, BMI was measured and a post-test was done. SPSS version 22 software was used for data analysis. Results There was no significant change in the BMI of students after the intervention in the control group (p = 0.476), but it decreased significantly in the test group (p < 0.001). Before the intervention, there was no statistically significant difference between the average score of health responsibility in the test group (54.63 $$\:±\:6.93$$ ± 6.93 ) and the control group (53.03 $$\:±\:$$ ± 6.79) (P = 0.370). After the intervention, the mean difference between the test group (62.56) and the control group (55.10) was statistically significant (P < 0.001). Before the intervention, about 70% of the students in both the test and control groups were at a relatively favorable health responsibility level. After the study, the number of students in the test group who were placed at a completely favorable level was almost twice as before, and a statistically significant difference was observed between the two groups(P = 0.035). Conclusions The results of the present study showed that virtual education during the outbreak of COVID-19 has led to an increase in the responsibility for the health of overweight and obese students (in terms of improving health behaviors, increasing the hours of physical activity, and modifying the eating pattern) and reducing the body mass index of students.